2020
DOI: 10.1111/aogs.14036
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and perinatal outcomes in consanguineous couples with a structural fetal anomaly: A cohort study

Abstract: Introduction Consanguineous unions occur when a couple are related outside marriage and is associated with adverse genetic and perinatal outcomes for affected offspring. The objectives of this study were to evaluate: (i) background characteristics, (ii) uptake of prenatal and postnatal investigation and (iii) diagnostic outcomes of UK consanguineous couples presenting with a fetal structural anomaly. Material and methods This was a retrospective and partly prospective cohort study comparing consanguineous (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Demographic characteristics and outcomes of the study cohort are shown in Table 1. The rates of South Asian ethnicity and consanguinity were above average owing to the underlying demographics of the region, as described previously 13 . All causative pathogenic (Class IV and V) variants and incidental findings with corresponding outcome are shown in Table 2; the reported VUS are displayed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Demographic characteristics and outcomes of the study cohort are shown in Table 1. The rates of South Asian ethnicity and consanguinity were above average owing to the underlying demographics of the region, as described previously 13 . All causative pathogenic (Class IV and V) variants and incidental findings with corresponding outcome are shown in Table 2; the reported VUS are displayed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…26 A recent study found that couples with consanguinity and Pakistani heritage were less likely to consent to invasive fetal testing and to genetic follow-up, which might make them more vulnerable to the risk of a pregnancy affected by congenital anomalies. 27 Therefore, the higher than expected proportion of children with South Asian heritage in our study could result from a combination of genetic predisposition and also parental views about pregnancy termination. Studies from the USA found lower survival rates with CHD in Black patients, 28 and with poorer socioeconomic circumstances in children with HLHS.…”
Section: Findings In Contextmentioning
confidence: 67%
“…Incidental findings present ethical challenges as they may detect adult‐onset disorders, such as cancer predisposition genes, which may introduce unanticipated anxiety into the family, as well as potentially leading to stigmatisation and a loss of autonomy for the future child. A trio exome may also uncover non‐paternity, which has an estimated median rate of around 4%, and consanguinity, where the rate is dependent upon regional demographics 41,42 . Consensus recommendations exist to support these challenging circumstances 19,43 .…”
Section: Ethical Challengesmentioning
confidence: 99%
“…A trio exome may also uncover nonpaternity, which has an estimated median rate of around 4%, and consanguinity, where the rate is dependent upon regional demographics. 41,42 Consensus recommendations exist to support these challenging circumstances. 19,43 Another important consideration for counselling is who has ownership of the results, which can pose a concern for the wider family and raise the question of who owns the genetic material as part of the 'joint account'.…”
Section: Ethical Challengesmentioning
confidence: 99%